Yayasan UMP call thought to be scammer - Nor Salwana, Mohammad Idris (2020)
Kuantan, 26 October 2020 - “I thought it was a call from a scammer when I got a phone call from Yayasan UMP saying I was chosen to receive Yayasan UMP Matriculation Excellence Incentive.” This statement was expressed by the new Universiti Malaysia Pahang (UMP) student, Fatin Ayu Kartika Mohd Suzaki, 20, who initially doubted the authenticity of the call she received from Yayasan UMP staff.